NALAR POLITIK KENEGARAAN DALAM ISLAM (Studi atas Pemikiran Muhammad Abiri>) - Yusdani, Yusdani (Analisis: Jurnal Studi Keislaman, 2011)
Discourse of  Islam vis-a-vis state is not apart from complexity  of Arabic and Islamic reason. Muh}ammad ‘A<bid al-Ja>biri showed that complexity  from  sources  of  thought  of  contemporary  socio-political science and sources of  Arab-Islamic tradition itself. According to him, democratic leader type of  Prophet is only applicative for Mecca and Medina  society.  Both communities  are recognized  applying  nomadic tribe system, and recruitment of  their leader was based on an adagium primus inter pares, just for the best and highly capable man can be elected by community. The past tradition cannot be applied wholly to present day without considering its socio-cultural aspect.